Social issues in television fiction - Henderson, Lesley (Edinburgh University Press, 2007)
Why are some controversial issues covered in TV soaps and dramas and not others? How are decisions really made 'behind the scenes'? How do programme makers push boundaries without losing viewers? What do audiences take away from their viewing experience? Does TV fiction have a greater impact on public understandings than TV news? This exciting new book draws on unique empirical data to examine the relationship between popular television fiction and wider society. The book gives lively and engaging insights into how and why socially sensitive story lines were taken up by different TV programmes from the late 1980s to the 2000s. Drawing on a series of case studies of medicine, health, illness and social problems including breast cancer, mental distress, sexual abuse and violence it comprehensively traces the path of storylines from initial conception through to audience reception and uses contemporary examples to link practice to theory. For the first time, this book addresses production and reception processes across a range of programmes and clearly demonstrates the ways in which television fiction plays a vital and powerful role in reflecting and shaping socio-cultural attitudes. Key Features nterviews with TV drama programme makers (producers, script writers and editors) detailed analysis of 'on screen' representation qualitative audience research using focus groups and innovative methods explores external influences on programme content including commercial imperatives, broadcast regulations, the role of campaigning organisations, wider media coverage. The book is essential reading for academics, researchers and students in the fields of media studies, sociology, cultural studies and communications. It will also be of interest to health communicators, social policy practitioners and broadcast professionals.